2020
DOI: 10.1200/jco.20.01076
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin and Paclitaxel for Advanced Endometrial Cancer: Final Overall Survival and Adverse Event Analysis of a Phase III Trial (NRG Oncology/GOG0209)

Abstract: PURPOSE Limitations of the paclitaxel-doxorubicin-cisplatin (TAP) regimen in the treatment of endometrial cancer include tolerability and cumbersome scheduling. The Gynecologic Oncology Group studied carboplatin plus paclitaxel (TC) as a noninferior alternative to TAP. METHODS GOG0209 was a phase III, randomized, noninferiority, open-label trial. Inclusion criteria were stage III, stage IV, and recurrent endometrial cancers; performance status 0-2; and adequate renal, hepatic, and marrow function. Prior radiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
145
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(154 citation statements)
references
References 19 publications
2
145
2
5
Order By: Relevance
“…Fleming et al, reported that the RR of PTX, cisplatin, and doxorubicin (TAP) regimens was 57% [ 8 9 ]. Similarly, Miller et al, [ 10 ] reported the RR of both PTX plus CBDCA (TC) and TAP to be approximately 50%. The RR of our trial treatment using one of the conventional TCs was expected to increase by 20%.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Fleming et al, reported that the RR of PTX, cisplatin, and doxorubicin (TAP) regimens was 57% [ 8 9 ]. Similarly, Miller et al, [ 10 ] reported the RR of both PTX plus CBDCA (TC) and TAP to be approximately 50%. The RR of our trial treatment using one of the conventional TCs was expected to increase by 20%.…”
Section: Methodsmentioning
confidence: 94%
“…Supposedly, the reason for these findings was that Katsumata et al, [ 12 13 ] and other researchers set the dosage of CBDCA to an AUC of 6 mg∙h/L. However, the number of patients was higher in the dd regimen group than in the conventional regimen group (n=113 vs. n=69) [ 9 10 ]. The ICON8 trial was set at an AUC of 5 or 6, based on the investigators' discretion [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, cytotoxic chemotherapies were the gold standard for metastatic endometrial cancer treatment, whatever the line of treatment. The first-line regimen for advanced EC is still the combination of carboplatin and paclitaxel with overall response rates (ORR) of 50 to 60%, median progression-free survival of one year, and a median overall survival slightly of above three years [40,41]. After platinum failure, mono-chemotherapies are routinely used with poor results.…”
Section: Immune Checkpoint Inhibitors In Ec Pd-(l)1 Inhibitors As Backbone Of All Strategies Under Investigationmentioning
confidence: 99%
“…The existing use of paclitaxel in ovarian [12], cervical [13] and endometrial [14] cancers is based on randomized phase 3 GOG-F studies. The first FDA approved agent in cervical cancer (topotecan) [15] and the first FDA approved targeted therapy in gynecologic cancer (bevacizumab in first-line metastatic cervical cancer) [16,17] are based on GOG-F studies.…”
Section: Track Record Of Successmentioning
confidence: 99%